Gejala Somatik dan Hubungannya Dengan Kecemasan dan Interosepsi - Maulina, Venie Viktoria Rondang; Ohira, Hideki (Faculty of Psychology, Universitas Surabaya, 2024)
In Somatic Symptom Disorder, individuals may misinterpret their symptoms as signs of disease. Meanwhile, interoception refers to an individual’s perception to sense internal body sensations. Interoception may play a role in the regulation of state and trait anxiety. Anxiety, in turn, is associated with somatic symptoms. A comprehensive study regarding somatic symptoms is still required to fill the knowledge gap regarding its relationships with other variables. In this study, 101 university students from Nagoya, Japan, fulfilled four questionnaires related to the study variables. The participants also completed the heartbeat counting task (HCT) to assess interoceptive accuracy and heart rate variability (HRV) measurement. The results showed that health concerns and trait anxiety are associated with somatic symptoms. In addition, the sub-scales Attention Regulation and Self-Regulation determined trait anxiety in an inverse correlation. These results suggest that interoception, particularly interoceptive sensibility, is negatively associated with trait anxiety regarding somatic symptoms. The inverse relationship could be expected, as interoceptive sensibility is a set of positive beliefs about aspects of the individual’s abilities and the tendency to consciously sense signals originating from inside their body.